The Role of Urban Marketing and Governance of Local Governments in Ecuador - Cevallos, Stefany (2020)
The role of urban marketing and the governance of local governments in Ecuador is analysed according to the Organic Code of Territorial Organization, Autonomy and Decentralization (COOTAD). The governance debate shows the potential that local governments can have in assuming this competence to attract Direct Foreign Investment (FDI). The mainstreaming of integrated quality in this work is the product of urban marketing in the construction of the branding or image of Ecuador and its economic positioning in the regional and international arena. It is concluded that the local government is coordinating commercial and institutional agendas in Public-Private Alliances (PPP) to ensure economic, socio-political and technological development in Ecuador.